Effects of cocoa polyphenol rich diet in prevention of colitis-associated colon cancer - Saadatdoust, Zeinab (2015)
Colorectal cancer (CRC) is the second highest mortality and the third most diagnosed in both men and women. Colitis-associated cancer is a subtype of CRC that is associated with inflammatory bowel disease. Cocoa has a rich source of polyphenols and inhibits the cancer cell proliferation and decrease the risk of different type of cancers, cardiovascular disease and diabetes. This study was aimed to determine the anti-cancer effects of cocoa rich diets on dextran sulfate sodium (DSS) and azoxymethane (AOM)-induced colitis associated cancer in BALB/c mice. Natural Forastero cocoa powder was used for this study and diets were prepared from an AIN-93G formulation. The 5% and 10% cocoa diets are produced by adding 50 g/kg and 100 g/kg cocoa to AIN-93G at the expense of starch, cellulose and casein. The total polyphenol content of the cocoa powder was determined. Cocoa rich diet was modified to supplement 1 g and 2 g of polyphenols per kg of diet respectively. Total number of 50 female BALB/c mice (Mus musculus) weighing 25- 30 g were divided into 5 different groups and each group consist of 10 mice. Data are presented as mean (n = 10 mice per group). The mice in groups 2, 3 and 4 were initiated by a single intraperitoneal (i.p.) injection of AOM (10 mg/kg body weight). Starting 1 week after the injection, 2% DSS in drinking water was administrated to mice of group 2, 3 and 4 for 7 days and 14 days and followed by normal drinking water for the recovery period. Totally 3 cycles of 2% DSS were treated. Group 1 (control) and Group 2 received AIN-93G diet, group 3 and 4 were treated with cocoa diet of 5% and 10%, respectively. Group 5 treated with 10% of cocoa diet alone to assess the toxicity of cocoa. On day 62 of the experiment, all mice were sacrificed and the entire colon and rectum were processed for histopathology examination and further evaluation. Pro-inflammatory mediators and cytokines were measured by enzyme-linked immunohistochemical assay; real-time–PCR and western blot analysis. The tissue samples were examined for ultrastructural changes in experimental mice by Transmission Electron Microscopy. Change in colon length in mouse model of colitis-associated cancer was significantly improved in animals receiving cocoa enriched diet. Spleen weight was significantly decreased in animals treated with cocoa diet (P<0.05). Colon tumor number was increased upon DSS/AOM administration and fed with cocoa-enriched diet showed reduced number of tumors/mice. Cocoa diet modulates histological alterations caused by AOM/DSS. Control and cocoa diet alone treated group of mice shown normal architecture of microvilli. AOM/DSS treated mice showing the invasive gland in the submucosa layer of a large size adenoma. Treatment 5% and 10% of cocoa-enriched diet showed small polyps in the muscular layer. In AOM/DSS group of animal, increased expressions of iNOS and COX-2 was observed by immunohistochemistry. However, treatment with 5% and 10% cocoa diet showed decreased expression of iNOS and COX-2, whereas control and cocoa alone groups showed fewer positive expressions. Deregulation of the JAK/STAT3 signaling pathway has also been implicated in colorectal tumorigenesis resulting in accumulation of cytokines and growth factors, Janus kinases.. Therefore, the potential of polyphenols in cocoa powder in targeting key components of the STAT3 signaling pathway along with iNOS and COX2 as a rational for cancer drug discovery was demonstrated. Colon tumors were further analyzed the mRNA levels of pro-inflammatory cytokines such as IL-6, TNF-α, IL-1β, IL-17 by RT-PCR and BcI-xL, Bax, Caspase 3 and Caspase 8 at protein levels by Western Blot analysis. It was shown that administration of cocoa significantly down-regulated inflammatory factors in colon cancer animal as compared with control (no cocoa treatment) (p<0.05). In summary, the ability of cocoa to prevent the development of the colon carcinogenesis was demonstrated by lower tumor incidence, number and size of DSS/AOM-treated mice. In this present study, shown that after cocoa-enriched diet, the colitis presented a statistical improvement and tumors burden decreased significantly, this was accompanied by lower activity of p-STAT3Y705, decreased expressions of COX-2 and iNOS, lower expression of cytokines in the colons of CAC mice. We suggest that the chemopreventive effect of cocoa enriched diet on colitis-associated carcinogenesis could be mediated mainly through the IL-6/STAT3 pathway. Taken together, the present data provide evidence that cocoa polyphenols would offer a natural approach to improve individual health status including the prevention of colonic inflammation with no toxicity.